Development and validation of a risk prediction model for post-polypectomy colorectal cancer in the USA: a prospective cohort study - Knudsen, Markus D.; Wang, Kai; Wang, Liang; Polychronidis, Georgios; Berstad, Paula; Wu, Kana; He, Xiaosheng; Hang, Dong; Fang, Zhe; Ogino, Shuji; Chan, Andrew T.; Giovannucci, Edward; et al. (EClinicalMedicine, 2023)
Background - Effective risk stratification tools for post-polypectomy colorectal cancer (PPCRC) are lacking. We aimed to develop an effective risk stratification tool for the prediction of PPCRC in three large population-based cohorts and to validate the tool in a clinical cohort. - Methods - Leveraging the integrated endoscopic, histopathologic and epidemiologic data in three U.S population-based cohorts of health professional (the Nurses' Health Study (NHS) I, II and Health Professionals Follow-up Study (HPFS)), we developed a risk score to predict incident PPCRC among 26,741 patients with a polypectomy between 1986 and 2017. We validated the PPCRC score in the Mass General Brigham (MGB) Colonoscopy Cohort (Boston, Massachusetts, U.S) of 76,603 patients with a polypectomy between 2007 and 2018. In all four cohorts, we collected detailed data on patients’ demographics, endoscopic history, polyp features, and lifestyle factors at polypectomy. The outcome, incidence of PPCRC, was assessed by biennial follow-up questionnaires in the NHS/HPFS cohorts, and through linkage to the Massachusetts Cancer Registry in the MGB cohort. In all four cohorts, individuals who were diagnosed with CRC or died before baseline or within six months after baseline were excluded. We used Cox regression to calculate the hazard ratio (HR), 95% confidence interval (CI) and assessed the discrimination using C-statistics and reclassification using the Net Reclassification Improvement (NRI). - Findings - During a median follow-up of 12.8 years (interquartile range (IQR): 9.3, 16.7) and 5.1 years (IQR: 2.7, 7.8) in the NHS/HPFS and MGB cohorts, we documented 220 and 241 PPCRC cases, respectively. We identified a PPCRC risk score based on 11 predictors. In the validation cohort, the PPCRC risk score showed a strong association with PPCRC risk (HR for high vs. low, 3.55, 95% CI, 2.59-4.88) and demonstrated a C-statistic (95% CI) of 0.75 (0.70-0.79), and was discriminatory even within the low- and high-risk polyp groups (C-statistic, 0.73 and 0.71, respectively) defined by the current colonoscopy surveillance recommendations, leading to a NRI of 45% (95% CI, 36-54%) for patients with PPCRC. - Interpretation - We developed and validated a risk stratification model for PPCRC that may be useful to guide tailored colonoscopy surveillance. Further work is needed to determine the optimal surveillance interval and test the added value of other predictors of PPCRC beyond those included in the current study, along with implementation studies. - Funding - US National Institutes of Health, the American Cancer Society, the South-Eastern Norway Regional Health Authority, the Deutsche Forschungsgemeinschaft.